(untitled) (REMUNOM, 2023)
In dentistry, biosafety standards aim to protect professionals and patients in the clinical environment in order to avoid infections, physical, chemical and biological risks. Their main purpose is to protect the performance of the dental surgeon, in the competence of handling instruments and products chemicals, techniques for handling sharps, sterilization and disinfection methods, antisepsis and asepsis and use of personal protective barriers. Therefore, it is essential that dentists constantly observe biosafety standards and asepsis and antisepsis precautions that aim to control and prevent cross-contamination. The objective of this study is to carry out a literature review on the general aspects of biosafety in oral surgery, highlighting the asepsis and antisepsis techniques performed in oral surgery. The search strategy was applied to the following databases: Virtual Health Library (VHL), SciELO and PubMed/Medline. It was possible to conclude that without preventive biosafety measures, dental offices can become serious sites of infection, since, in addition to the great possibility of cross-infections, the equipment, materials, locations, and even the patient without due preparation can cause serious infectious risks.